Pigmented Villonodular Synovitis of the Temporomandibular Joint: A Unique Presentation. Issue 4 (April 2016) - Pianosi, Kiersten; Rigby, Matthew; Hart, Robert; Trites, Jonathan; Taylor, S. Mark
Abstract : Summary: Pigmented villonodular synovitis (PVNS) is a rare and benign proliferative disorder of synovium with potentially locally aggressive growth and invasion of the bone. Occurring within the joints, tendon sheaths, and bursae, it is most commonly a monoarticular disease affecting large joints. In particular, most cases of PVNS occur in the knee. PVNS of the temporomandibular joint (TMJ) is a highly rare disorder, with approximately 60 cases reported. Herein, we present a unique case of an elderly male presenting with ear pain and subsequently diagnosed with PVNS of the TMJ with a history of trauma to the area. Initial imaging of the TMJ and the surrounding region looked concerning for invasive and/or malignant disease, but an open biopsy confirmed PVNS.